Merjenje izometričnosti presadka sprednje križne vezi kolena (LCA) - Veselko, Matjaž (Medicinski razgledi, 2000)
A reconstructed anterior cruciate ligament should allow normal motion and stability of the knee. An accurate placement of the graft is mandatory to prevent slackening, deformation or rupture of the graft, or limitation of the range of knee motion. We studied the influence of orientation of the femoral attachment on the distribution of loads on the graft during knee motion. Side-to-side isometricity of a 10 mm wide graft in two extreme orientations ofthe graft femoral attachments was studied on a cadaveric specimen. In experiment A, the femoral attachment was parallel to the inner wall of the lateral femoral condyle, in sagittal plane. In experiment B, the femoral attachment was in frontal plane. The mean value for the maximal side-to-side difference in fiber length change was much smaller in experiment B, the difference being statistically significant. The study showed that the femoral attachment of the ACL graft oriented in frontal plane provides a more uniform distribution of load throughout the range of knee motion.
Keywords: Anterior cruciate ligament; kolenski sklep; križne vezi; Transplantation; transplantacija; Biomechanics; biomehanika; Cadaver; Femur; Tibia